A "two-in-one" integrated electrode design for high-energy rechargeable bipolar Li batteries. Issue 21 (23rd May 2022) - Liu, Qianqian; Liu, Yan; Xu, Yifei; Wang, Jianghao; Chen, Zerui; Wu, Hao Bin
Abstract : A novel bipolar battery architecture using an integrated Al electrode as both the high-capacity anode and bipolar plate is proposed to construct bipolar Li batteries, leading to high energy density and simple architecture/manufacturing. Abstract : Bipolar design is a promising strategy to achieve rechargeable batteries with high voltage output and improved energy density. However, the development of bipolar Li batteries has been hampered by the lack of desirable bipolar plates and complicated fabrication procedure. Herein, we demonstrate the use of Al foil as a "two-in-one" integrated electrode, which functions as both the anode and bipolar current collector to construct bipolar Li batteries. With optimized Al foil and electrolyte, the Li alloying reaction proceeds uniformly on the anode side of the Al electrode with high reversibility. Such a design minimizes the ancillary components and simplifies the cell architecture, leading to 20% increase in the volumetric energy density and easy manufacturing. As a proof of concept, the two-unit bipolar LPF|Al cell displays a reversible capacity of 157 mA h g −1 with a discharge voltage plateau of 5.9 V and stable cycling performance. Moreover, such a bipolar design is universal for various cathode materials, providing a promising approach toward high-energy rechargeable batteries.